Vitamin-D deficiency predicts infections in young north Indian children: A secondary data analysis - Chowdhury, Ranadip; Taneja, Sunita; Bhandari, Nita; Sinha, Bireshwar; Upadhyay, Ravi Prakash; Bhan, Maharaj Kishan; Strand, Tor A. (PloS one, 2017)
Recent studies have demonstrated a relationship between poor vitamin D status and respiratory infections and diarrhea among young children. Acute lower respiratory infections (ALRI) and diarrhea are among the two most important causes of death in under-5 children. In this paper, we examined the extent to which vitamin-D deficiency (<10 ng/ml) predicts ALRI, clinical pneumonia and diarrhea among 6 to 30 months old children. We used data from a randomized controlled trial (RCT) of daily folic acid and/or vitamin B12 supplementation for six months in 6 to 30 months old children conducted in Delhi, India. Generalized estimating equations (GEE) were used to examine the associations between vitamin-D deficiency and episodes of ALRI, clinical pneumonia and diarrhea. Of the 960 subjects who had vitamin-D concentrations measured, 331(34.5%) were vitamin-D deficient. We found, after controlling for relevant potential confounders (age, sex, breastfeeding status, wasting, stunting, underweight, anemia status and season), that the risk of ALRI was significantly higher among vitamin-D deficient (OR 1.26; 95% CI: 1.03 to 1.55) compared to vitamin-D-replete children in the six months follow-up period. Vitamin-D status was not associated with episodes of diarrhea or clinical pneumonia. Vitamin-D deficiency is common in young children in New Delhi and is associated with a higher risk of ALRI. The role of vitamin D in Indian children needs to be elucidated in further studies.